Developing data production maps: meeting patient discharge data submission requirements. (1st September 2004) - Davidson, Bruce; Lee, Yang W.; Wang, Richard
Recent research in information quality management concluded that firms must manage information as a product, and that the entire information manufacturing system must be managed in order to enable firms to assure delivery of information products with high quality. In this paper, we report a longitudinal case study in a major hospital on how data production maps are developed and used to improve the quality of information products. Specifically, we focus on data production maps for patient discharge data. These data production maps have enabled this hospital to model, analyse, and improve the quality of patient-level data that must be submitted to the State Department of Health Services annually. Implications and lessons learned are also discussed.